EFFECTS OF CONVERSATIONAL HYPNOSIS ON RELATIVE PARASYMPATHETIC TONE AND PATIENT COMFORT DURING AXILLARY BRACHIAL PLEXUS BLOCKS FOR AMBULATORY UPPER LIMB SURGERY:A Quasiexperimental Pilot Study. Issue 2 (3rd April 2018) - Boselli, Emmanuel; Musellec, Hervé; Bernard, Franck; Guillou, Nicolas; Hugot, Pierre; Augris-Mathieu, Caroline; Diot-Junique, Nathalie; Bouvet, Lionel; Allaouchiche, Bernard
Abstract: This two-center quasiexperimental pilot study was to determine the effect of conversational hypnosis on patient comfort and parasympathetic tone, which may represent a quantitative measure of hypnotic depth, during regional anesthesia. The patients received conversational hypnosis in one center and oral premedication in the other. The patients' subjective comfort (0-10 rating scale) and objective parasympathetic tone, as assessed by the Analgesia/Nociception Index (ANI), were measured before and after regional anesthesia. The parasympathetic tone and comfort scores evidenced a significantly greater increase in the hypnosis patients than in controls. These findings suggest that using conversational hypnosis during regional anesthesia may be followed by a subjective increase in patient comfort and an objective increase in parasympathetic tone, monitored by ANI.